FIQH MUAMALAH ANALYSIS OF DEFERRED FERTILIZER TRANSACTIONS IN BALUKANG DONGGALA - Sahrin, Moh; Aisya, Sitti; Kristiane, Desy (Program Studi Hukum Ekonomi Syariah, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2024)
This study examines the practice of borrowing and lending fertilizer and rice seeds with an agreement to pay after the harvest in Balukang Village, Sojol District, Donggala Regency, as well as its perspective in Islamic commercial law (fiqh muamalah). The aim of this research is to identify this practice within the community and analyze it from the perspective of fiqh muamalah. The method used is a juridical-sociological approach, with data collection techniques including observation, documentation, and in-depth interviews. The findings show that this practice has become a tradition in Balukang Village, where fertilizer and seeds are provided at the beginning of the contract, with payment made after the harvest in the form of rice. The agreement is made orally and recorded by the creditor without a written contract. This practice is more accurately described as a sale agreement with deferred payment, although the community commonly refers to it as a borrowing and lending arrangement. From the perspective of fiqh muamalah, this practice is allowed because it has become a customary practice that does not harm either party and has been mutually agreed upon by both parties. Abstrak Penelitian ini membahas praktik utang piutang pupuk dan benih padi dengan perjanjian pembayaran setelah panen di Desa Balukang, Kecamatan Sojol, Kabupaten Donggala, serta perspektif fikih muamalah terhadap praktik tersebut. Tujuan penelitian ini adalah untuk mengidentifikasi praktik tersebut di masyarakat dan menganalisisnya dari sudut pandang fikih muamalah. Metode yang digunakan adalah pendekatan yuridis sosiologis, dengan teknik pengumpulan data berupa observasi, dokumentasi, dan wawancara mendalam. Hasil penelitian menunjukkan bahwa praktik ini telah menjadi kebiasaan di Desa Balukang, di mana pupuk dan benih diberikan pada awal akad dengan pembayaran setelah masa panen dalam bentuk beras. Perjanjian dilakukan secara lisan dan dicatat oleh kreditur tanpa adanya perjanjian tertulis. Praktik ini seharusnya dianggap sebagai akad jual beli dengan pembayaran ditangguhkan, meskipun masyarakat umumnya mengenalnya sebagai utang piutang. Dari perspektif fikih muamalah, praktik ini diperbolehkan karena sudah menjadi kebiasaan yang tidak merugikan pihak manapun dan telah disepakati oleh kedua belah pihak.